Computational characterization and control of electrical conductivity of nanowire composite network under mechanical deformation. Issue 1 (December 2018) - Hwang, Jinyoung; Sohn, Hiesang; Lee, Sang
Abstract Quantitative models to predict the electrical performance of 1-D nanowire (NW) composite networks under external deformation such as bending and patterning are developed by Monte-Carlo based computations, and appropriate solutions are addressed to enhance the tolerance of the sheet resistance (Rs ) of the NW networks under the deformation. In addition, several strategies are employed to improve further the robustness of the sheet resistance against the network deformation. In the case of bending, outstanding bending durability of a hybrid NW network coated on a 2-D sheet is confirmed with a numerical model, and a network of NWs aligned unidirectionally toward bend axis is introduced to alleviate the sheet resistance degradation. In the case of a narrowly patterned channel, the conductivity enhancement of a network of NWs aligned in parallel to the channel with reduced channel is validated, and a network made with two types of NWs with different lengths is suggested to enhance the tolerance of the electrical conductivity. The results offer useful design guidelines to the use of the 1-D NW percolation network for flexible transparent conducting electrodes.